Proposal for a computer-assisted analysis of lawful interceptions of communication. Issue 1 (2nd January 2016) - Frazzica, Giovanni
Abstract : This paper presents the potential for the analysis of texts when applied to interceptions carried out with the help of next-generation software. In order to do this, after a brief explanation of some of the main procedures, the article presents the results of an investigation into text data extracted from wiretapping and in-person conversations found in judicial documents. The amount of data, obtained through wiretapping and the use of bugs, has made it possible to gather important information about the dynamics that characterise how criminal organisations work. The use of wiretaps and bugs are, therefore, vital tools without which it would undoubtedly not have been possible to achieve the results now apparent to everyone. Thanks to a careful analysis, it has been possible to reconstruct the kind of relationships between the members of organised crime, highlighting the roles they hold and the strategies used for territorial control.